Acoustic mapping velocimetry. Issue 5 (27th May 2016) - Muste, M.; Baranya, S.; Tsubaki, R.; Kim, D.; Ho, H.; Tsai, H.; Law, D.
Abstract: Knowledge of sediment dynamics in rivers is of great importance for various practical purposes. Despite its high relevance in riverine environment processes, the monitoring of sediment rates remains a major and challenging task for both suspended and bed load estimation. While the measurement of suspended load is currently an active area of testing with nonintrusive technologies (optical and acoustic), bed load measurement does not mark a similar progress. This paper describes an innovative combination of measurement techniques and analysis protocols that establishes the proof‐of‐concept for a promising technique, labeled herein Acoustic Mapping Velocimetry (AMV). The technique estimates bed load rates in rivers developing bed forms using a nonintrusive measurements approach. The raw information for AMV is collected with acoustic multibeam technology that in turn provides maps of the bathymetry over longitudinal swaths. As long as the acoustic maps can be acquired relatively quickly and the repetition rate for the mapping is commensurate with the movement of the bed forms, successive acoustic maps capture the progression of the bed form movement. Two‐dimensional velocity maps associated with the bed form migration are obtained by implementing algorithms typically used in particle image velocimetry to acoustic maps converted in gray‐level images. Furthermore, use of the obtained acoustic and velocity maps in conjunction with analytical formulations (e.g., Exner equation) enables estimation of multidirectional bed load rates over the whole imaged area. This paper presents a validation study of the AMV technique using a set of laboratory experiments. Key Points: Acoustic mapping velocimetry is a novel method to measure riverine bed load transport indirectly The method combines optical and acoustic techniques A proof‐of‐concept experiment for AMV is presented